Personality-mediated speed-accuracy tradeoffs in mating in a 17-year periodical cicada. (7th September 2022) - Roth, Allison M; Kent, Sarah M; Hobson, Elizabeth A; Kritsky, Gene; Nakagawa, Shinichi
Abstract: There exists growing evidence that animal personality (consistent between individual differences in behavior) can influence an individual's fitness. Furthermore, limitations in behavioral plasticity may cause personality-mediated tradeoffs to occur, for example, between speed and accuracy in decision making. We explored whether various measures of personality could predict speed-accuracy tradeoffs in mate selection using Pharaoh cicadas ( Magicicada septendecim ) and examined the phenotypic traits predicting male mating performance and advertisement rates. We assessed whether male exploration behavior, boldness, and weight could predict a male's overall copulation attempt rate (the number of attempted copulations with conspecifics of either sex), the number of errors a male made when selecting a mate (the number of same-sex copulation attempts), and male reproductive performance (whether a male successfully copulated with a female). We also assessed whether personality-dependent variation in male advertisement rate (the number of calling song bouts) might underpin the correlation between exploration behavior and mating performance. Although male exploration behavior did not predict male advertisement rate, we found that faster-exploring males exhibited higher overall rates of attempted copulations while also attempting more same-sex copulations, compared to slower-exploring males, suggesting a personality-mediated speed-accuracy tradeoff. Despite making more mate choice errors, however, faster explorers were more likely to successfully copulate with females, compared to slower explorers, indicating that speed may be favored over accuracy in systems where heavily male-biased sex ratios lead to scramble competition. Overall, this work highlights the role of personality in sexual selection and demonstrates that personality can influence speed-accuracy trade-offs in mating. Abstract : Animal personality can have important fitness consequences. Personality may also mediate tradeoffs between speed and accuracy in decision-making. We found that faster- versus slower-exploring male Pharaoh cicadas attempted to mate at higher rates but also attempted more same-sex copulations (i.e., they made more mate choice errors). Despite this increased propensity for mate choice errors, faster explorers were more likely to mate successfully with females, indicating that speed is favored over accuracy in this system.